Bias Gender dalam Novel Dua Garis Biru Karya Lucia Priandarini - Efdilla, Tasya; Nurizzati, Nurizzati (Lembaga Yasin AlSys, 2026)
This study aimed to describe the forms of gender bias, their causal factors, and their impacts in the novel Dua Garis Biru by Lucia Priandarini. A descriptive qualitative approach was employed, with data collected through close reading and note-taking of words, phrases, clauses, and sentences that represent gender bias through narrative, dialogue, and characters’ actions. Data were analyzed using a descriptive–analytical method by classifying them into categories of forms of gender bias, causal factors, and impacts, and then interpreting them through the lenses of feminist literary criticism and social psychology to uncover power relations within the text. The validity of the data was tested using theory triangulation. The findings reveal diverse forms of gender bias, including gender stereotypes, paternalism, marginalization, subordination, verbal abuse, excessive workload, objectification, and discrimination. The causal factors of gender bias are influenced by patriarchal culture and tradition, socio-structural conditions, gender norms and stereotypes, as well as the influence of mass media and technology. The impacts of gender bias are reflected in humiliation and stigma, loss of autonomy, social isolation, damaged self-esteem, limited educational and career opportunities, and emotional violence. These findings affirm that Dua Garis Biru represents unequal gender relations and functions as a medium of social reflection on gender injustice in society.